Thermal and pressure stability of myrosinase enzymes from black mustard (Brassica nigra L. W.D.J. Koch. var. nigra), brown mustard (Brassica juncea L. Czern. var. juncea) and yellow mustard (Sinapsis alba L. subsp. maire) seeds. (15th November 2015) - Okunade, Olukayode Adediran; Ghawi, Sameer Khalil; Methven, Lisa; Niranjan, Keshavan
Highlights: Brown mustard has higher myrosinase specific activity than other mustard varieties. Brown & black mustard myrosinase is more thermal & pressure stable than the yellow one. Low pressure application (200–400 MPa) decreases myrosinase thermal inactivation rate. Abstract: This study investigates the effects of temperature and pressure on inactivation of myrosinase extracted from black, brown and yellow mustard seeds. Brown mustard had higher myrosinase activity (2.75 un/mL) than black (1.50 un/mL) and yellow mustard (0.63 un/mL). The extent of enzyme inactivation increased with pressure (600–800 MPa) and temperature (30–70 °C) for all the mustard seeds. However, at combinations of lower pressures (200–400 MPa) and high temperatures (60–80 °C), there was less inactivation. For example, application of 300 MPa and 70 °C for 10 min retained 20%, 80% and 65% activity in yellow, black and brown mustard, respectively, whereas the corresponding activity retentions when applying only heat (70 °C, 10 min) were 0%, 59% and 35%. Thus, application of moderate pressures (200–400 MPa) can potentially be used to retain myrosinase activity needed for subsequent glucosinolate hydrolysis.